Non-urgent care in the hospital medical emergency department in France: how much and which health needs does it reflect?. Issue 4 (August 1996) - Lang, T; Davido, A; Diakité, B; Agay, E; Viel, J F; Flicoteaux, B
Abstract : OBJECTIVES: The goal was to describe the use of the medical emergency department as a source of non-urgent medical care in order to assess unmet health care needs among its users. The specific objectives were thus to assess the proportion of emergency department visits for non-urgent medical care and to describe those who used the department for this reason. DESIGN: A cross sectional study was performed at the emergency department in two hospitals (around 12, 000 visits per year each). Subjects were interviewed before and after the visit using a standardised questionnaire. SETTING: The medical emergency department of two university hospitals, one in Paris and one in Besançon (France). SUBJECTS: Each patient aged 15 and more attending the emergency department for a visit during 40 randomly selected periods of 12 hours was included. MAIN OUTCOME MEASURES: A definition of urgent care was adopted before the beginning of the study. Four expert judgments were then used for each case to determine whether the reason for the visit was urgent or not. RESULTS: Altogether 594 patients in the Paris emergency department and 614 in the Besançon one were included. In Besançon, the patients were older, a general practitioner was more often cited as the regular source of care, and the percentage of subsequent hospital admission was higher than in Paris (71% versus 34%). The non-urgent visits were estimated to account for 35% and 29% of the visits in Paris and Besançon respectively. Patients using the emergency department for a non-urgent visit were younger than other patients. More of them were unemployed, homeless, born outside of France, and without health insurance. CONCLUSIONS: Non-urgent use of the emergency department was observed in about one third of the visits. Groups using the department for primary care and/or non-urgent care were mostly young and socially fragile, with no regular source of health care. Their poor health condition suggests that there is a need for a structure providing primary care both inside and outside 'normal' working hours.